Microwave Assisted Synthesis of New Heterocyclic Compounds: 1,2,3-Triazoles and Tetrazoles and Study of Their Biological Activity - I. Mohammed, Adnan; H. Dawood, Ashour; F. Ali, Khalid; AL-Mosawi, Mohsen (Asian Journal of Chemistry, 2012)
The work includes synthesis of 1,2,3-triazoles via click conditions and using the microwave irradiation starting from two synthesized azides: 2,3,4,6-tetra-O-acetyl-b-D-glucopyranosyl azide (5) and perfluorobutylethyl azide (10) and different terminal alkynes. It also includes microwave enhanced synthesis of tetrazoles via the reaction of two synthesized azides i.e., perfluorobutylethyl azide (10) and 1,5-diazidopentane (13) with benzoyl cyanide. Most of the prepared compounds have been characterized by: TLC, FT-IR, 1H NMR, 13C NMR, LC-MS and microelemental analysis.